2000
DOI: 10.1016/s0009-2614(00)00105-6
|View full text |Cite
|
Sign up to set email alerts
|

OH detection by absorption of frequency-doubled diode laser radiation at 308 nm

Abstract: Radiation at 308 nm has been obtained by frequency doubling the output of a commercial diode laser cooled to 165 K. A single pass through a crystal of LiIO converted 1 mW of 616 nm radiation to 50 pW of UV, and this was used to detect the 3 OH radical in absorption in a flow tube. Possible extensions of the method for detection of OH in the atmosphere are discussed. q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Barry et al 110 reported development of UV CW laser source applicable to CRDS or CEA detection of OH at 308 nm. They also noted one of the major complications to this approach, the formation of OH from the reaction of water vapor with O ( 1 D) formed from photolysis of ambient O 3 by the laser light within the cavity.…”
Section: Hydroxyl Radicalmentioning
confidence: 99%
“…Barry et al 110 reported development of UV CW laser source applicable to CRDS or CEA detection of OH at 308 nm. They also noted one of the major complications to this approach, the formation of OH from the reaction of water vapor with O ( 1 D) formed from photolysis of ambient O 3 by the laser light within the cavity.…”
Section: Hydroxyl Radicalmentioning
confidence: 99%
“…A high pulse-repetition-frequency (PRF), of the order of several kHz, is therefore required to obtain sufficient signal to detect the extremely low atmospheric OH concentrations on a suitably short timescale. Although all-solid-state laser systems have been developed in the laboratory for the detection of OH, 15,16 the 308 nm radiation required for field measurement of atmospheric OH by LIF has hitherto been generated via frequency doubled dye laser systems, with the high PRF provided by pumping the dye with copper-vapour lasers (CVL) [7][8][9][10] or solid state Nd:YAG (neodymium:yttrium-aluminium-garnet) lasers. 11,13,17 The CVL/dye laser systems exhibit disadvantages of complexity and wet chemical requirement (dyes) and large bulk (y 3 6 2 6 0.5 m instrument footprint), high power consumption (5 kW with the requirement of threephase power), and long warm-up time (y 1 h).…”
Section: Introductionmentioning
confidence: 99%
“…There are some very compact instruments undergoing development in the laboratory, for example cavity ring-down spectrometers or locked cavity absorption techniques using small continuous diode lasers, that may become suitable for measurements of free-radicals (Bakowski et al, 2002;Brown, 2003). The idea of intracavity laser spectroscopy for ultra-sensitive detection of atmospheric OH was first suggested in 1991 (McManus & Kolb, 1991) but only around 2000 have suitable continuous wave laser sources at 308 nm become available (Barry et al, 2000).…”
Section: Future Directionsmentioning
confidence: 99%